Nutrition Supports Deconstructed and Disrupted: An Evaluation of a Multilevel School-Based Intervention during the Time of COVID - Rachael D. Dombrowski (MDPI AG, 2021)
The Best Food Forward (BFF) project aims to provide multiple nutrition supports and interventions to improve family food security (FS) and health outcomes associated with FS within two metropolitan school districts. A quasi-experimental time-series design guided a multilevel evaluation for BFF through surveys, biometric screenings, focus groups, and observations among a random sample of caregiver–child dyads. FS, utilization of school meal programs, and nutrition behaviors were observed and analyzed at three time points: preintervention, postintervention pre-COVID-19, and postintervention post-COVID-19. Participants included 122 parents and 162 youth. Families reported (1) an income less than $35,000 annually (48.8%) and (2) a COVID-19-related job loss (36.9%). Parents used Supplemental Nutrition Assistance Programs or Women, Infants, Children benefits prior to (51.1%) and following COVID-19 (50.0%). No significant differences in FS were found. RM-ANOVA indicated an increase in breakfast consumption at home and a decrease in use of the school breakfast program (F(1.78, 74) = 19.64, p < 0.001, partial η2 = 0.21) and school lunch program (F(1.51, 74) = 23.30, p < 0.001, partial η2 = 0.24). Rates of FS and eating behaviors did not change significantly over time. Correlations of program usage and eating behaviors demonstrate the importance of promoting participation in school meal programs. BFF may have prevented significant decreases in FS during COVID-19.